Exploring the Impact of Self-Leadership on Work Motivation and Nursing Performance - Prastito, Firman Prastito; Suminar, Ervi; Fitrianur, Widya Lita (Universitas Muhammadiyah Gresik, 2024)
Background: Self-leadership is a process that exists within a person to increase motivation and direct himself to behave in a way that is in accordance with what other people expect of him. Individuals who have self-leadership are able to build themselves up in achieving their goals and to provide the needed direction and/or support to ensure that their goals are aligned with the general goals of the group or organization. The purpose of this study was to determine the relationship between Self Leadership and work motivation and performance of nurses. Methods: The design of this study was an analytic descriptive study with a cross sectional approach with a population of 86 nurses and a sample of 71 nurses, using a simple random sampling technique. The instrument in this study used a questionnaire. The analysis in this study used the Spearman Rho correlation test (p <0.05). Results: The results of the study show that there is a very significant relationship between self- leadership and work motivation. The level of relationship is very high in the number of respondents 71 people with r correlation = 0.618 (r minimum 0.234). The statistical test shows that p = 0.000 so that p < α (0.05) which means that the hypothesis (H1) is accepted. And from the test results there is a very significant relationship between self-leadership and nurse performance. The level of relationship is very high in the number of respondents 71 people with r correlation = 0.620 (r minimum 0.234). The statistical test shows that p = 0.000 so that p < α (0.05) which means that the hypothesis (H1) is accepted. Conclusion: There is a Relationship between Self Leadership on Work Motivation and Nurse Performance at Muhammadiyah Gresik Hospital. Keywords: Self Leadership, Work Motivation, Performance